A Rapid and Low-Cost PCR Thermal Cycler for Infectious Disease Diagnostics - Chan, Kamfai (PLoS One, 2016)
The ability to make rapid diagnosis of infectious diseases broadly available in a portable, low-cost format would mark a great step forward in global health. Many molecular diagnostic assays are developed based on using thermal cyclers to carry out polymerase chain reaction (PCR) and reverse-transcription PCR for DNA and RNA amplification and detection, respectively. Unfortunately, most commercial thermal cyclers are expensive and need continuous electrical power supply, so they are not suitable for uses in low-resource settings. We have previously reported a low-cost and simple approach to amplify DNA using vacuum insulated stainless steel thermoses food cans, which we have named it thermos thermal cycler or TTC. Here, we describe the use of an improved set up to enable the detection of viral RNA targets by reverse-transcription PCR (RT-PCR), thus expanding the TTC’s ability to identify highly infectious, RNA virus-based diseases in low resource settings. The TTC was successful in demonstrating high-speed and sensitive detection of DNA or RNA targets of sexually transmitted diseases, HIV/AIDS, Ebola hemorrhagic fever, and dengue fever. Our innovative TTC costs less than $200 to build and has a capacity of at least eight tubes. In terms of speed, the TTC’s performance exceeded that of commercial thermal cyclers tested. When coupled with low-cost endpoint detection technologies such as nucleic acid lateral-flow assay or a cell-phone-based fluorescence detector, the TTC will increase the availability of on-site molecular diagnostics in low-resource settings.